19. EFFICACY OF SUFENTANIL AND FENTANYL IN GENERAL ANESTHESIA FOR TONSILLECTOMY IN CHILDREN (Vietnam Journal of Community Medicine, 2024)
Background: Tonsillectomy is one of the most common surgeries in children, performed under general anesthesia and associated with severe postoperative pain. Using opioid not only have an effect on intraoperative pain but also on postoperative pain. The aim of this study was to evaluate the efficacy of Sufentanil and Fentanyl in general anesthesia for tonsillectomy in children.Methods: A descriptive study was conducted on 119 patients aged 2-16 years with ASA physical status I or II, undergoing elective tonsillectomy, randomly assigned to receive either 0.3 µg/kg Sufentanil or 2 µg/kg Fentanyl for induction. Quality of endotracheal intubation was assessed based on heart rate and blood pressure changes before and after intubation, and intubation scoring scale. Postoperative agitation in children was evaluated using an agitation scoring scale. Pain intensity was assessed using the FPS-R at 2, 4, and 6 hours postoperatively, and by the PPPM-SF at 24 hours, along with recording any adverse effects.Results: Excellent and good quality of endotracheal intubation was achieved in 100% and 92.6% of the Sufentanil and Fentanyl groups, respectively (p < 0.05). The incidence of postoperative agitation was 23.1% in the Sufentanil group and 40.7% in the Fentanyl group (p < 0.05). Severe agitation occurred in 3.1% of the Sufentanil group compared to 18.5% in the Fentanyl group (p < 0.05). The FPS-R pain scores at 2, 4, 6 hours postoperatively and the PPPM-SF pain score at 24 hours were lower in Sufentanil group in compare with Fentanyl group (p < 0,05).Conclusion: Sufentanil or Fentanyl provides effective analgesia in general anesthesia for tonsillectomy in children. Sufentanil group had better intubation quality, less postoperative agitation, and better postoperative analgesia than Fentanyl group.
Keywords: Sufentanil; Fentanyl; agitation; pain; children; tonsillectomy